Development of a Cognitive Training Support Programme for prevention of dementia and cognitive decline in at-risk older adults - de Jager Loots, Celeste A.; Price, Geraint; Barbera, Mariagnese; Neely, Anna Stigsdotter; Gavelin, Hanna M.; Lehtisalo, Jenni; Ngandu, Tiia; Solomon, Alina; Mangialasche, Francesca; Kivipelto, Miia (Frontiers in Dementia, 2024)
Background: Evidence for the beneficial effects of cognitive training on cognitive function and daily living activities is inconclusive. Variable study quality and design does not allow for robust comparisons/meta-analyses of different cognitive training programmes. Fairly low adherence to extended cognitive training interventions in clinical trials has been reported. Aims: The aim of further developing a Cognitive Training Support Programme (CTSP) is to supplement the Computerised Cognitive Training (CCT) intervention component of the multimodal Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER), which is adapted to different cultural, regional and economic settings within the Word-Wide FINGERS (WW-FINGERS) Network. The main objectives are to improve adherence to cognitive training through a behaviour change framework and provide information about cognitive stimulation, social engagement and lifestyle risk factors for dementia. Methods: Six CTSP sessions were re-designed covering topics including 1)CCT instructions and tasks, 2)Cognitive domains: episodic memory, executive function and processing speed, 3)Successful ageing and compensatory strategies, 4)Cognitive stimulation and engagement, 5)Wellbeing factors affecting cognition (e.g. sleep, mood), 6)Sensory factors. Session content will be related to everyday life, with participant reflection and behaviour change techniques incorporated, e.g. strategies, goal-setting, active planning to enhance motivation and adherence to the CCT and in relevant lifestyle changes. Conclusions: Through interactive presentations promoting brain health, the programme provides for personal reflection that may enhance capability, opportunity and motivation for behaviour change. This will support adherence to the CCT within multidomain intervention trials. Efficacy of the programme will be evaluated through participant feedback and adherence metrics.